2017
DOI: 10.1371/journal.pone.0187424
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the polymerase-γ theory: Production of ROS as a mode of NRTI-induced mitochondrial toxicity

Abstract: Use of some HIV-1 nucleoside reverse transcriptase inhibitors (NRTI) is associated with severe adverse events. However, the exact mechanisms behind their toxicity has not been fully understood. Mitochondrial dysfunction after chronic exposure to specific NRTIs has predominantly been assigned to mitochondrial polymerase-γ inhibition by NRTIs. However, an increasing amount of data suggests that this is not the sole mechanism. Many NRTI induced adverse events have been linked to the incurrence of oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 92 publications
(121 reference statements)
2
20
0
Order By: Relevance
“…The NRTI-associated decrease in mtDNA leads to altered mitochondrial function, which in turn results in decreased ATP production, reduced mitochondrial membrane potential, increased ROS production, and modifications of the respiratory chain enzyme activity [126, 127]. Besides inhibiting mtDNA replication, NRTIs can also directly damage mitochondrial enzymes, enhancing the generation of ROS production [127]. Indeed, an increase in oxidative stress has been frequently associated with antiretroviral treatment in HIV patients [128-130].…”
Section: Art and Mitochondriamentioning
confidence: 99%
“…The NRTI-associated decrease in mtDNA leads to altered mitochondrial function, which in turn results in decreased ATP production, reduced mitochondrial membrane potential, increased ROS production, and modifications of the respiratory chain enzyme activity [126, 127]. Besides inhibiting mtDNA replication, NRTIs can also directly damage mitochondrial enzymes, enhancing the generation of ROS production [127]. Indeed, an increase in oxidative stress has been frequently associated with antiretroviral treatment in HIV patients [128-130].…”
Section: Art and Mitochondriamentioning
confidence: 99%
“…The myopathy was thought to be closely related to mitochondrial toxicity. This was supported by some findings in muscle biopsies of patients receiving ART therapy, such as mitochondrial defect, decreased oxidative phosphorylation (OXPHOS) activity and decreased mitochondrial DNA (mtDNA) level [21,22]. Early studies on non-nucleotide reverse transcriptase inhibitors (NRTI) drugs have shown that they exert very minimal effects on DNA polymerase alpha, but affect beta and gamma polymerase to several degrees.…”
Section: Antiretroviral-induced Mitochondrial Dysfunctionmentioning
confidence: 86%
“…In this condition, NRTIs disturb mitochondrial function via other mechanisms such as nucleoside homeostasis disturbance caused by the pharmacokinetics of NRTIs. NRTIs can also directly inhibit mito chondrial enzymes, which may increase the generation of ROS [22][23][24][25].…”
Section: Hiv Antigen and Apoptosismentioning
confidence: 99%
“…Indeed, Taura et al reported that LPV was the most potent inducer of ROS production in PBMCs among the PIs [ 38 ]. This production was recently shown to be an alternative mechanism of NRTI-dependent mitochondrial toxicity [ 66 ]. Even if the downstream consequences of the ROS production in this context is not clearly established, mtDNA damage might represent a side effect of LPV/r treatment.…”
Section: Discussionmentioning
confidence: 99%